Recovery of Functional Status After Stroke in a Tri-Ethnic Population - Berges, Ivonne-M. (2012)
OBJECTIVE: To examine recovery of functional status for white, black, and Hispanic patients who have had a stroke from the time of admission to inpatient medical rehabilitation to 12 months after discharge. DESIGN: A longitudinal study that used information from the Stroke Recovery in Underserved Population database, a prospective observational study of persons with stroke who received inpatient medical rehabilitation services during 2005-2006. SETTING: Eleven inpatient rehabilitation facilities located across diverse regions of the United States, including California, Florida, Iowa, Illinois, Kentucky, New Jersey, New York (2), Texas (2), and Washington, DC. PARTICIPANTS: A total of 990 adults aged 55 years or older who had a stroke and were admitted to 1 of 11 inpatient medical rehabilitation facilities in the United States were interviewed at 4 time points, including admission to and discharge from an inpatient medical rehabilitation facility and 3 and 12 months after discharge. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURE: Functional status as measured by the Functional Independence Measure (FIM). RESULTS: For the total sample, FIM ratings increased from admission to discharge and from discharge to 3-month follow-up, with little recovery occurring between 3 and 12 months. In random effects mixed models, at 3-month follow-up, both black and Hispanic patients had lower FIM ratings than did white patients. At 12-month follow-up, black and white patients were similar; however, Hispanic patients continued to have lower FIM ratings compare with white patients. Racial/ethnic group, age, length of stay, and medical comorbidities were significant predictors of total FIM ratings over the 4 time points. CONCLUSIONS: Persons 55 years and older who have had a stroke, regardless of race/ethnicity, appear to benefit from inpatient medical rehabilitation. Most functional status gains occur during inpatient medical rehabilitation and continue in the first few months after discharge, with little change afterward.